2016
DOI: 10.1155/2016/1879529
|View full text |Cite
|
Sign up to set email alerts
|

Scedosporiosis in a Combined Kidney and Liver Transplant Recipient: A Case Report of Possible Transmission from a Near-Drowning Donor

Abstract: Scedosporium spp. are saprobic fungi that cause serious infections in immunocompromised hosts and in near-drowning victims. Solid organ transplant recipients are at increased risk of scedosporiosis as they require aggressive immunosuppression to prevent allograft rejection. We present a case of disseminated Scedosporium apiospermum infection occurring in the recipient of a combined kidney and liver transplantation whose organs were donated by a near-drowning victim and review the literature of scedosporiosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…Risk factors for scedosporiosis include: CF, [254][255][256] severe immunosuppression, 241 hematological malignancy (especially with neutropenia), 254,[257][258][259] OTR, 14,55,72,241,245,254,257,[260][261][262] HIV/ acquired immune deficiency syndrome (AIDS), 263,264 and near drowning. 265 Scedosporium rarely affects healthy individuals 266,267 but bone/joint, 268,269 ear, 270,271 and SSTI 272 have been reported in immunocompetent persons following trauma, surgery, or inoculation injury 241,257,269 or near drowning.…”
Section: Risk Factors For Scedosporiosismentioning
confidence: 99%
“…Risk factors for scedosporiosis include: CF, [254][255][256] severe immunosuppression, 241 hematological malignancy (especially with neutropenia), 254,[257][258][259] OTR, 14,55,72,241,245,254,257,[260][261][262] HIV/ acquired immune deficiency syndrome (AIDS), 263,264 and near drowning. 265 Scedosporium rarely affects healthy individuals 266,267 but bone/joint, 268,269 ear, 270,271 and SSTI 272 have been reported in immunocompetent persons following trauma, surgery, or inoculation injury 241,257,269 or near drowning.…”
Section: Risk Factors For Scedosporiosismentioning
confidence: 99%
“…Disseminated infections with S. apiospermum/Pseudallescheria and pneumonia or CNS involvement can follow near-drowning accidents in polluted water 171 , 177 185 . Of note are cases of transplant recipients with previously near-drowning victims as donors 186 , 187 . In contrast, Lomentospora prolificans (formerly Scedosporium prolificans , or S. inflatum ) is mainly isolated from cases with underlying immunosupression 188 .…”
Section: Rare Moldsmentioning
confidence: 99%
“…9 The S.aurantiacum infections may be cutaneous, respiratory, central nervous system or disseminated. 9 S. aurantiacum is inherently resistant to amphotericin, therefore voriconazole represents first line treatment. 7 Co-infection and co-colonization of scedosporium species and P.aeruginosa has been well documented, but the presence of S. aurantiacum was not detected until later in the patient's illness.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of scedosporium infection is generally poor, with an expected overall survival of less than 50% in solid organ transplant recipients. 9 Further research into the underlying mechanism of immunosuppressive agent related PAP is required to deepen our understanding of PAP and improve treatment options. Moreover, in-vitro studies have J o u r n a l P r e -p r o o f shown GM-CSF may augment the anti-fungal function of macrophages against fungal infections 9 , hinting toward a shared underlying pathophysiology of PAP and fungal infections.…”
Section: Discussionmentioning
confidence: 99%